Stimulating innovation in products and services : - Kaufman, J. Jerry (Wiley-Interscience, 2006)
In this groundbreaking book, internationally acclaimed authors demonstrate that innovation can be mastered via systematic and replicable methods. Following careful instructions and guidelines, readers discover how to foster the ingenuity that resides within all organizations and how it can be most efficiently and effectively used to create value.